Pengaruh Globalisasi dan Modernisasi Hukum Waris di Indonesia - Irene Septia Fada; Achmad Tanthowi; Dwi Noviani (Student Research Journal, 2024)
This research explores the impact of globalization and modernization on inheritance law in Indonesia, a fundamental legal aspect of the socio-economic life of society. Globalization introduces international legal values and principles that interact with national laws, driving more inclusive and equitable reforms. On the other hand, legal modernization aims to update and simplify inheritance law procedures and regulations, making them more relevant and accessible in the digital age. Using qualitative methods with a descriptive analytical approach, this research analyzes data from legal literature, legislation, and interviews with legal practitioners and academics. The findings show that globalization and modernization have a significant impact, ranging from aligning inheritance laws with international standards to increasing efficiency through digitalization. However, this process also faces challenges such as cultural resistance and infrastructure issues. This article concludes that while globalization and modernization present significant opportunities to enhance justice and accessibility in inheritance law, a sensitive adaptation to the local context is essential to ensure broad acceptance and effective implementation.